ON THE HUMANE DIMENSION OF CONTEMPORARY ARMED CONFLICTS THROUGH NUMBERS AND THE LAW (Годишен зборник на Филозофски факултет - Скопје, 2023)
The re-examination of the classification of modern armed conflicts is done through the analysis of humanitarian law and the available data on armed conflicts, by combining the legal, political and ethical dimensions of war and the statistical indicators of modern conflicts.The author answers the questions about: Defining the conflict according to the various philosophical, social and legal criteria with the cultural, legal and political basis of the war and the corresponding reasons for the occurrence and prolongation of the conflicts; and the main trends of the conflicts through the numerous presences of the conflicts on the global scene, the number of victims, the regional displacement of the conflicts and the role of the Islamic State.In the analysis of the conflicts, the complexity of the modern conflicts through the expanded categories of victims and combatants, as well as the need for the protection of the victims, are emphasized.Hence the research touches on the issue of the applicability of the legal and illegal combatant categories and the corresponding immunity that follows them.Researching the trends of modern armed conflicts cannot avoid the ethical dimensions surrounding the category of child soldiers. From a methodological point of view, the problem of determining precise statistics for the indirectly killed civilians, who continue to represent the largest category, remains unsolved.